Predisposition of Women to Cardiovascular Diseases: A Side-Effect of Increased Glucocorticoid Signaling During the COVID-19 Pandemic? - Dhaibar, Hemangini A.; Cruz-Topete, Diana (Frontiers in Global Women's Health, 2021)
The novel coronavirus disease 2019 (COVID-19) pandemic has created a significant health crisis worldwide. To mitigate this disease's spread, “social distancing” and “shelter in place” have been implemented. While these actions have been critical to controlling the pandemic, they have short- and long-term mental health consequences due to increased stress. There is a strong association between mental stress and cardiovascular disease (CVD). Young women (pre-menopausal) are at high risk of developing CV events in response to mental stress compared to age-matched men. The mechanisms underlying women's increased reactivity and response to stress are mostly unknown. The present review summarizes the known physiological consequences of mental stress in women's CV health and the latest molecular findings of the actions of the primary stress hormones, glucocorticoids, on the CV system. The current data suggest a clear link between psychological stress and heart disease, and women have an increased sensitivity to the harmful effects of stress hormone signaling imbalances. Therefore, it is expected that with the given unprecedented levels of stress associated with the COVID-19 pandemic, women's CV health will be significantly compromised. It is critical to widen our understanding of the direct contribution of mental stress to CVD risk in women and to identify biochemical markers with predictive value for CVD in female patients with/without cardiovascular conditions who have experienced significant mental stress during the current pandemic.